INJIL MENYELAMATKAN ORANG BERDOSA - SERI ANTONIUS - (Universitas Asahan, 2020)
Gospel Saved Sinners. This article is a literature study that describes concept of Christian’s salvation in the view and teaching of God's word. The author seeks various information from library resources related to the research topic which presented descriptively. The concept of Christian’s salvation based on the word of God is different from the concept of salvation based on the view of religion in general and also view of certain church. Understanding the notion of salvation in Christianity today has experienced a shift and seems to have been narrowed down with various understandings that are not in accordance with the nature and understanding of salvation in the Bible (especially according to Romans). Sin is essentially a violation of the law that God has set for humans, sin makes men apart from God. In Romans, Paul emphasizes that the work of God carried out in Christ and accepted by faith, results in our justification or restoration of relationship with God.